Análise biomecânica, de fatores de treinamento, testes clínicos e desfechos autorrelatados na dor patelofemoral: uma investigação em diferentes populações - Machado, Eliane de Morais (Universidade Federal de São Carlos, 2025)
The central theme of this thesis was the study of patellofemoral pain (PFP), a common condition in both runners and the general population. PFP is characterized by self- reported pain in the anterior aspect of the knee, which is exacerbated by activities such as stair climbing, squatting, running, or prolonged kneeling. The prognosis of PFP is unfavorable, often persisting for many years and reducing the overall quality of life of those affected. It is associated with biomechanical factors (from the hip, knee, ankle, and foot) that alter joint loading. Despite investigations, there are inconsistencies regarding the role of these variables. Our hypothesis is that one of the reasons for this inconsistency is the type of analysis conducted: linear approaches, which do not account for the interaction between multiple factors nor the coupling between lower limb joints, and therefore may fail to capture the multifactorial nature of this condition. The treatment of PFP, whether in runners or the general population, primarily aims to improve functionality. In clinical settings, function is typically assessed using self-reported measures (such as Anterior Knee Pain Scale (AKPS), and Knee Injury and Osteoarthritis Outcome Scale (KOOS)) and objective measures of functional performance (clinical tests such as squatting, stair ambulation and single leg hop tests), which provide complementary information. Although clinical tests are commonly used, the relationship between performance in these tests and the outcomes reported in recommended questionnaires remains unclear. Based on the above, the present thesis aimed to explore these ideas through three studies: Study 1 investigated how kinematic variables, training characteristics, and demographic data interact in the occurrence of PFP in runners; study 2 compared lower limb coordination and coordination variability between male and female runners with and without PFP; and study 3 explored how changes in clinical tests of squat and stair ascent/descent are associated with changes in patient-reported outcomes (PROMs) in individuals with PFP following treatment. The results of the first study indicate that running training factors (weekly running distance and self-selected running speed) interacted with lower limb kinematic variables (knee abduction peak and ankle dorsiflexion peak) in distinct ways to differentiate between runners with and without PFP. In the second study, differences in coordination patterns were observed between men and women without PFP in the couplings between femoral internal/external rotation and foot eversion/inversion, as well as femoral abduction/adduction and foot eversion/inversion. Differences were also found between men with and without PFP in the couplings between femoral abduction/adduction and foot eversion/inversion, and femoral and tibial flexion/extension. Overall, men without PFP exhibited coordination patterns indicating a more efficient proximal-distal coordination compared to women without PFP and men with the condition. Only the coupling between femoral and tibial flexion/extension showed a difference in coordination variability, with male runners with PFP displaying greater variability than those without pain. This finding contradicts the theory that lower coordination variability is associated with pathological states during running. Finally, the third study demonstrated a positive relationship between improvements in clinical tests of stepping (up and down) and patient-reported outcomes, with the stair ascent test contributing most to the explained variance, while the squat test showed no significant correlation. These findings highlight the importance of combining objective measures with self-reported patient outcomes. The overall results of this thesis indicate that, regardless of the population, clinical assessment and condition monitoring should be individualized, addressing the specific needs of each patient.
Biomechanical analysis, training factors, clinical tests, and self-reported outcomes in patellofemoral pain: an investigation in different populations
Keywords: Avaliação; Dor anterior no joelho; Desfechos autorrelatados; Sistemas complexos; Assessment; Anterior knee pain; Patient reported outcomes; Complex systems; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL